Implementation of the Free Nutritious Meal Program in Pinrang Regency:A Qualitative Study from an Islamic Legal Perspective - Bahri ZR, Syamsul; Anugrah Pradana, Syafa'at (CV. Dyoqu Publishing Management, 2025)
Background: The Free Nutritious Meal Program (MBG) in Pinrang Regency requires an analysis of its implementation and legal regulations from a Siyasah Syar'iyyah perspective. Aims: This study aims to determine the implementation of the MBG Program and its implementing legal regulations in Pinrang Regency through Siyasah Syar'iyyah analysis. Method: The type of research is qualitative field research. Data was obtained from primary and secondary sources, through observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Result: The implementation of the MBG Program in Pinrang proceeded through planning, implementation, and monitoring stages. Its implementation received high participation from the school and parents. The involvement of local MSMEs has also been proven to help the local economy. The legal basis for this program refers to Law No. 18/2012 (Food), Law No. 17/2023 (Health), and Presidential Regulations No. 83/2017 & 2024. Conclusion: The MBG program is a form of public welfare (maslahah 'ammah) that is valid according to sharia. This policy aligns with the maqasid sharia principle of preserving the soul (hifz al-nafs) and the mind (hifz al-'aql), with the goal of improving health, reducing stunting, and improving the quality of human resources for the younger generation